Ambiente informatizado: para o aprofundamento da função quadrática por alunos da 2ª série do ensino médio - Santos, Sergio Aparecido dos (2009)
The purpose of this study was to develop a computerized environment turned to teaching, in order to favor the deepening of the knowledge related to the polynomial function of second degree. In this environment, there is a sequence of activities that approaches the graphical representation of polynomial functions of second degree. It is based on the principles of the Instructional Design methodology that uses five phases; analysis, design, development, implementation and evaluation and, based on the Theory of Semiotics Representation Register by Raymond Duval and on the Situation Theory. The sequence of activities held in the environment was guided by a research done by a research done by Maia, about the teaching of the quadratic function, using the Winplot software and the articulation between the graphical and algebraic registers. These computer tools were used: GEIOGEBRA and NVU, being, the former; to develop the sequence and the latter; to create the environment and its interactions. The environment was implemented with 12th graders of a public school in the Great São Paulo, in the city of Carapicuíba. The protocols of three students that took part actively of all discussion in the study group were analyzed. The results obtained lead us to conclude that the computerized environment and the activities contained in it favors the understanding of the register articulations of algebraic and graphical representation and a deepening of knowledge related to the polynomial function of the second degree